PENGARUH PERENCANAAN PAJAK, PERTUMBUHAN PENJUALAN DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR BASIC MATERIALS YANG TERDAFTAR DI BURSA EFEK INDONESIA DARI TAHUN 2019-2023) - Isjayanti, Cicih; Yusuf, Nur’Aini (Publika Citra Media, 2025)
This research aims to determine the effect of tax planning, sales growth, capital structure on company value. The population in this study was 102 companies in the basic materials sector listed on the Indonesia Stock Exchange (BEI) in 2019 - 2023. The sample was determined based on the purposive sampling method, so that 24 companies were obtained during the 5 year research period. This type of research uses quantitative research with secondary data sources, namely company annual reports obtained through the official BEI website www.idx.co.id. The data processing uses eviews 12. The results of the research show that tax planning, sales growth and capital structure simultaneously influence company value. Partially, tax planning and capital structure variables have no effect on company value. Meanwhile, sales growth affects company value.